2000
DOI: 10.1620/tjem.190.129
|View full text |Cite
|
Sign up to set email alerts
|

The Vasocontractive Action of Norepinephrine and Serotonin in Deep Arterioles of Rat Cerebral Gray Matter

Abstract: To examine the direct effects of norepinephrine (NE) and serotonin (5-HT) on the contractility of arterioles in the gray matter of the rat cerebrum, we micro-perfused arterioles in vitro and observed the changes in luminal diameter under the stop-flow condition with constant intraluminal pressure. While the average diameter of the lumen of arterioles was 39.9 +/- 9.7 microm (n=7) in Hepes-buffered saline, the average in 10(-7) M NE in the extraluminal solution changed into smaller in saline by 21.1 +/- 5.4% (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Earlier investigators reported that ␣-adrenergic catecholamines vasoconstricted cerebral and pial arterioles (31)(32)(33)(34). These effects have been proved either in the superficial cerebral area, observed through cranial windows (33), or in the deep cerebral area of the cerebrum and hippocampus (35).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier investigators reported that ␣-adrenergic catecholamines vasoconstricted cerebral and pial arterioles (31)(32)(33)(34). These effects have been proved either in the superficial cerebral area, observed through cranial windows (33), or in the deep cerebral area of the cerebrum and hippocampus (35).…”
Section: Discussionmentioning
confidence: 97%
“…Ritsuko Takahashi et al 29 microperfused arterioles from deep gray matter of rats. They found that norepinephrine caused a dose-dependent vasoconstriction when the concentration exceeded 10 −7 M. Wahl et al 30 added norepinephrine to the perivascular space with micropipettes and observed the cerebral vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 62 animal studies identified, the majority of cases measured CBF response to NE and other agents, utilizing: autoradiographic diffusible tracer technique, electromagnetic flow probe, freely diffusible tracers, thermal diffusion probe, clearance method, laser‐Doppler flow velocity, radioactive gas elimination, radioactive microsphere, flow transducer and flow meter, visual recording software, and two other methods. The animal models studied included baboons (3), 17‐19 cats (8), 20‐27 dogs (11), 28‐38 goats (3), 39‐41 pigs (12), 42‐53 sheep (1), 54 mice (1), 55 rabbits (5), 56‐60 rats (17) 61‐77 and one retrospective study 16 with dogs, cats, rats, and humans. The characteristics of the animal studies can be seen in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%